2012
DOI: 10.4236/wja.2012.24036
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with First-Line Antiretroviral Therapy Failure amongst HIV-Infected African Patients: A Case-Control Study

Abstract: Background: Since 2001, anti-retroviral therapy (ART) has been provided to over 75,000 HIV-infected patients at the USAID-Academic Model Providing Access to Healthcare (AMPATH) Partnership in western Kenya. Over 1000 of these patients have switched to second-line ART. We therefore set out to determine factors associated with first-line ART failure amongst these patients. Methods: This case controlled study matched patients (in the ratio 1:2) from the electronic AMPATH Medical Record System on the basis of age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
29
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 30 publications
10
29
1
Order By: Relevance
“…This was supported by a study conducted in Cameron [36] in which patients initiated with d4t has increased risk of toxicity. However, this finding was contradicted with the results reported by a study conducted in Kenya [37] in which d4t has a decreased risk of treatment failure as compared to AZT. The risk of composite outcomes was not statistically significant on d4t with any of the NNRTI drugs when lost patients were assumed censored.…”
Section: Discussioncontrasting
confidence: 59%
“…This was supported by a study conducted in Cameron [36] in which patients initiated with d4t has increased risk of toxicity. However, this finding was contradicted with the results reported by a study conducted in Kenya [37] in which d4t has a decreased risk of treatment failure as compared to AZT. The risk of composite outcomes was not statistically significant on d4t with any of the NNRTI drugs when lost patients were assumed censored.…”
Section: Discussioncontrasting
confidence: 59%
“…17 Studies from Ethopia and Kenya reported that the choice of NRTI (NVP vs EVF) was not associated treatment failure. 30,36 In the present study authors found that 74.1% (40/54) patients who had FLA, had very low baseline CD4 count (<100 cells/mm3) at initiation of ART. These patients might have very high baseline viral load as compared to the patients who had higher CD4 count at initiation.…”
Section: Discussionsupporting
confidence: 47%
“…30 Present study findings were in contrast with the study by Kowbah CM et al, from Kenya who showed that Zidovidine based regime was associated with more treatment failure. 36 Stavudine is more susceptible to develop drug resistance on prolonged therapy as compare to zidovudine. Resistance to stavudine arise through specific pathways that involve either selection of the 151M mutation or insertion of two serine or serinealanine residues at amino acid residue 69.…”
Section: Discussionmentioning
confidence: 99%
“…Kwobah et al [21] identified that non adherence was associated with almost three times the odds of treatment failure and Gonzalez-Serna et al [22] found that an adherence level greater than or equal to 95% independently reduced treatment discontinuation by 61%. Ickovics et al [14] have reported that HIV/AIDS patients whose degree of adherence was less than 95% were 3-5 times more likely to have treatment failure compared to those with adherence levels of 95% or higher and treatment failure is one of the most common reasons to switch therapy [25].…”
Section: Discussionmentioning
confidence: 99%
“…Many HIV studies [21,22] so far have looked at treatment failure and discontinuation of ART from the perspective of temporal trends or taxonomy of possible determinants. The present study aims to elucidate a possible association between insufficient adherence to ART and treatment change among HIV/AIDS patients at the Korle-Bu Teaching Hospital in Ghana.…”
Section: Introductionmentioning
confidence: 99%